Law's Infamy : Understanding the Canon of Bad Law - Umphrey, Martha Merrill; Douglas, Lawrence; Sarat, Austin (Book collections on Project MUSE., 2021)
"This book takes up the question of whether and how to tell the story of the law's infamy. It examines when and why the word infamy should be used to characterize legal decisions or actions taken in the name of the law. It does so while acknowledging that law's infamy by no means a familiar locution. More commonly the stories we tell of law's failures talk of injustices not infamy. Labelling a legal decision infamous suggests a distinctive kind of injustice, one which is particularly evil or wicked. Doing so means that such a decision cannot be redeemed or reformed; it can only be repudiated"--